China's Africa policy: opportunity and challenge for European development cooperation - Sven Grimm; Thomas Fues; Denise Laufer (Deutsches Institut für Entwicklungspolitik (DIE), 2006)
China's headlong rise to the status of a world power is leading to some profound changes in the global system: Indeed, we can say that a new multipolar order is in the making. The consequences of this transformation are impressively evident in Africa. China's expanding presence there is contributing to the continent's economic upturn and enlarging political spaces of African governments. At the same time, though, the events involved here entail risks for Africa's long-term development perspectives as well as for regional efforts in the areas of human rights, democracy, and sustainability. In geopolitical, economic, and development terms, the China factor is altering the basic parameters on which the West's relations with Africa are based. In the context of the ongoing discussion on a strategic partnership with the People's Republic of China, the European Union (EU) is actively seeking a constructive-critical dialogue with the country. If the Millennium Development Goals (MDGs) are to be reached, it will be essential that Europe and China – despite differences in their values and interests, and based on African priorities – deepen their exchange on their development programs and explore what opportunities may be given to cooperate in Africa. Ultimately, it is the African partners themselves who will have to decide on what offers of cooperation they may be inclined to make use of in the future.
Keywords: 330